2021
DOI: 10.3389/fbuil.2021.622382
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Urban Heating Under Land-Cover and Climate Change Scenarios in Indonesia: Application of the Universal Thermal Climate Index

Abstract: Climate change causing an increase of frequency and magnitude of heat waves has a huge impact on the urban population worldwide. In Indonesia, the Southeast Asian country in the tropical climate zone, the increasing heat wave duration due to climate change will be also magnified by projected rapid urbanization. Therefore, not only climate change mitigation measures but also adaptation solutions to more frequent extreme weather events are necessary. Adaptation is essential at local levels. The projected increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previous research has also revealed that high heat stress index values are concentrated primarily in the central and densely populated areas [2]. Moreover, owing to the UHI effects, urban areas experience higher land surface temperatures than rural areas [2,21]. Despite this, high heat exposure was observed on the east coast of North Sumatra, along the coast of East Java, and in the southern part of Bali.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous research has also revealed that high heat stress index values are concentrated primarily in the central and densely populated areas [2]. Moreover, owing to the UHI effects, urban areas experience higher land surface temperatures than rural areas [2,21]. Despite this, high heat exposure was observed on the east coast of North Sumatra, along the coast of East Java, and in the southern part of Bali.…”
Section: Discussionmentioning
confidence: 98%
“…Economic growth in sectors such as manufacturing, agriculture, and tourism has resulted in expanding urban areas in those regions. Previous research has also revealed that high heat stress index values are concentrated primarily in the central and densely populated areas [2]. Moreover, owing to the UHI effects, urban areas experience higher land surface temperatures than rural areas [2,21].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Surabaya's urban park development program is one of the causes of this positive change in land use and cover. Setiawati et al (2021) reported that from 1995 to 2016 the bare land in the southwestern and central part of Surabaya was converted into green parks. Furthermore, the increase in minimum, average, and maximum surface temperatures in 2015 and 2019 is in line with the percentage of land use change into built-up areas (64%) supported by changes in water bodies and green areas to agricultural land at 6.5% and 4.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%